Pengembangan Motif Aceh dan Penataan Ruang Kerja Bagi Pengrajin Souvenir - Wira Dharma; Anita Ruzana (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in national economic development because they also play a role in the distribution of development results in addition to playing a role in economic growth and employment. In the economic crisis that has occurred in our country since a few years ago, where many large-scale businesses have stagnated and even stopped their activities, the Micro, Small, and Medium Enterprises (MSMEs) sector has proven to be more resilient in dealing with this crisis. UMKM companies in the Aceh handicraft sector located in the city of Banda Aceh can produce products that have export opportunities or are indirectly brought out of the country, namely Malaysia. Thailand, America, Australia, Dubai, London, South Africa, and Singapore, therefore, need to apply the right business development strategy to face competition and be recognized by the wider community, one way to implement a competitiveness strategy is to carry out coaching. and guidance on the production process for UKM Riska Souvenir Aceh, especially on the aspects of work stations and the development of Acehnese motifs.